The Complex Reality and Trans-disciplinary Approach in World of Higher Education - Lubis, Akhyar Yusuf (Manunggal Halim Jaya, 2024)
This paper discusses the transdisciplinary approach and its importance to be discussed and applied in the world of higher education research to understand and address the complexity of socio-cultural problems. Gillez Deleuze and Felix Guattari through a famous book, A Thousand Plateaus proposed two terms